Indian parents’ perspective of maintaining heritage language in the metropolitan Jakarta - Munmun Gupta (Universitas Katolik Indonesia Atma Jaya, 2020)
The present study examines the role of Indian parents residing in Indonesia in maintaining heritage languages at home. The report presents parents' attitudes towards languages and the strategies used by these parents to promote heritage-language maintenance (HLM) while residing in Indonesia. Two research instruments were used: a questionnaire and a semi-structured interview. 23 Indian respondents (22 mothers and 1 father) residing in Jakarta participated in an online survey. Four participants volunteered for a follow-up interview to explore their language beliefs and attitudes. The majority of these parents regard Hindi or other Indian regional languages to be their heritage language, yet they use English to communicate with their children because of the ease—and lack of time to teach their children their heritage language. They also valorize English and the learning of other languages because of the benefits they entail, such as a better future and economic stability. Most of these parents agree that preserving and maintaining their heritage language is vital; however, they have only been somewhat successful in maintaining it.